If $ -1 < x < 0,$ then $sin^{-1}x $ equals |
$\pi - sin^{-1}\sqrt{1-x^2}$ $tan^{-1}\frac{x}{\sqrt{1-x^2}}$ $-cot^{-1}\left(\frac{\sqrt{1-x^2}}{x}\right)$ none of these |
$tan^{-1}\frac{x}{\sqrt{1-x^2}}$ |
Let $sin^{-1}x = \theta $. Then , x = sin $\theta $. Now, $-1 < x < 0 ⇒ -\frac{\pi}{2} < \theta < 0 $ $\pi - sin^{-1}\sqrt{1-x^2}$ $= \pi - sin^{-1} (cos \theta )$ $= \pi - sin (\frac{\pi}{2}+\theta ) = \pi - (\frac{\pi}{2}+\theta )=\frac{\pi}{2}+\theta $ As - $\frac{\pi}{2} < \theta < 0$ $∴ 0< \pi - \theta <\frac{\pi}{2} ⇒ 0 < \pi 0 sin^{-1}\sqrt{1-x^2} < \frac{\pi}{2}$ $∴ sin^{-1} x ≠ \pi - sin^{_1} \sqrt{1-x^2}$ So, option (a) is not correct. We have, $tan^{-1}\frac{x}{\sqrt{1-x^2}}$ $tan^{-1}\left(\frac{sin\theta}{\sqrt{1-sin^2\theta }}\right)=tan^{-1} (tan \theta )= \theta = sin^{-1}x.$ Thus, option (b) is correct. |